Hubungan Dukungan Keluarga Terhadap Kemampuan Perawatan Diri (Self Care) Pada Anak Retardasi Mental Di SLB - Septiyana Yuliyanti; Siti Lestari; Rinda Intan Sari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Mental retarded children refer to children with special needs and under-average IQ. One of the most observable problems in children is - the incapability to carry out routine activities and self-care. Objectives: This research determined the correlation between family support and the self-care level of mentally retarded children at a special school. Method: This quantitative research applied a cross-sectional approach. The sample consisted of 36 children aged between 7 and 17 years old. The researchers took the sample with a total sampling technique. Then, the researchers analyzed the data with Spearman’s rank. Results: The characteristics of the male children are aged 10 years old. The parents are mostly middle adult individuals. They were mostly female with Senior High School education. They were housewives. The obtained p-value was 0.001, indicating the correlation between family support and the self-care level of the mentally retarded children. Suggestion: The results described the family support of children with retarded mental to improve their self-care autonomously.